Implementation Of Kafalah Dhamman & Selling In Buying And Selling - Fadillah Balqish Ramadhan; Tarisa Mufidah; Muhammad Nur Iqbal (Jurnal Multidisiplin Sahombu, 2025)
Study This discuss two types contract in transaction service in perspective jurisprudence transactions , namely caravan dhaman ( guarantee ) and jua'alah ( reward for services ). Research objectives This is For understand concepts , characteristics , and applications second contract the in practice Islamic economics through library research approach . Research methods This depend on study library from books , articles journals , and sources relevant Islamic law . Kafalah dhaman is agreement involving​ guarantee payment or settlement obligation from party guarantor ( kafil ) if the guaranteed party ( makful ' alayh ) fails fulfil obligations . Contract This aiming For provide a sense of security for the party that does transaction , because existence guarantee settlement obligation from party third . Instead , go for it is contracts that focus on giving reward on a service or successful achievement​ achieved . Rewards given after designated party​ succeed fulfil task or agreed conditions , with​ objective For push achievement objective certain in public or business . Research results show that although second contract This own difference fundamental in purpose and its application , both reflect principle base in Islamic economics , namely justice and transparency in transaction .